Effects of Ni/Cu replacement on improvement of tensile and hydrogen-embrittlement properties in austenitic stainless steels. (15th August 2022) - Cho, Hyung-Jun; Cho, Yeonggeun; Gwon, Hojun; Lee, Sunghak; Sohn, Seok Su; Kim, Sung-Joon
Abstract: Effects of Ni/Cu replacement and subsequent aging treatment on tensile and hydrogen embrittlement (HE) properties were investigated in Fe-Cr-Ni austenitic stainless steels. With the Ni/Cu replacement, tensile strength and ductility were reduced in the as-annealed state by the increased stacking fault energy (SFE), whereas they were enhanced in the aged state due to the consumption of Cu in the matrix by the precipitation and resultantly lowed SFE. After the electrochemical H-charging, the H permeation depth decreased in the aged Cu-containing steels, indicating that Cu-rich precipitates effectively interfered the diffusion of H to increase the HE resistance. However, the excessive formation of Cu-rich precipitates destabilized the austenite phase, and induced the martensitic transformation. This α'-martensite preferably formed inside or at intersections of deformation twins, along with austenite grain boundaries, thereby providing H-induced crack propagation paths. These cracks caused the earlier brittle fracture and severe HE as a consequence. This result would suggest that the formation of Cu-rich precipitates by replacing expensive Ni could enhance both tensile properties and HE resistance, but a delicate control of SFE should be required to overcome the trade-off relationship of strength and HE resistance. Graphical abstract: Image, graphical abstract